Health Care Access and Prevalence of the Metabolic Syndrome Among Elders Living in High-Altitude Areas of the Mediterranean Islands: The MEDIS Study (The Review of Diabetic Studies, 2023)
AIM: The aim of the present work was to evaluate the relationships between sociodemographic, clinical, and lifestyle characteristics and the presence of metabolic syndrome, among high and low altitude living elderly individuals without known CVD. METHODS: During 2005-2011, 1959 elderly (aged 65 to 100 years) individuals from 13 Mediterranean islands were enrolled. Sociodemographic, clinical, and lifestyle factors were assessed using standard procedures. Metabolic syndrome was defined according to the (Adult Treatment Panel) ATP III criteria. Mountainous areas were defined those more than 400 meters in height. RESULTS: For the present analysis 713 men and 596 women were studied; the prevalence of the metabolic syndrome was 29% (24% in men, 35% in women, p < 0.001). Furthermore, the prevalence of metabolic syndrome was 55% in the elders living in mountainous areas, as compared with 26% among those living at sea-level (p = 0.01). Similarly, the prevalence of hypertension, hypercholesterolemia, and obesity were higher in high altitude as compared with low altitude areas (all pvalues < 0.01). After adjusting for various confounders, elders living in high altitude areas were 3.06-times more likely to have the metabolic syndrome than those living at sea-level (OR = 3.06, 95%CI 2.02-4.65). However, when the annual number of visits to health care centers was taken into account, the effect of altitude of living was not associated with the presence of the syndrome. CONCLUSIONS: A considerable proportion of mountainous living elderly had the metabolic syndrome. Public health actions need to be taken to reduce the burden of cardiometabolic disorders by enabling better access to health care, especially in remote mountainous rural areas.